ЭФФЕКТИВНОЕ ИСПОЛЬЗОВАНИЕ СОЛНЕЧНОЙ ЭНЕРГИИ В ТЕПЛИЦАХ - Курбонов, Б.Э. (SCIENCE and SOCIETY, 2024)
The article deals with the issues of effective connection of solar radiation heating barrier coefficients and heat accumulation indicators as a function of geometrical parameters and solar radiation reception.